1997
DOI: 10.1097/00005392-199703000-00125
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity in Primary Prostate Cancer

Abstract: The present results indicate that telomerase activity might be a marker for detecting malignancy of the prostate and evaluating the malignant potential of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
102
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 13 publications
12
102
0
1
Order By: Relevance
“…In some series, telomerase activity was associated with lower grade and lower stage BC [84,90]. Other studies pointed out that both telomerase activity [70] and telomerase expression [126] are associated with higher stage and higher grade [70,90]. Preliminary evidence obtained in cell lines suggest that BC might have TERT promoter mutations [53].…”
Section: Telomerase Promoter Mutations In Bladder Carcinomasmentioning
confidence: 99%
See 2 more Smart Citations
“…In some series, telomerase activity was associated with lower grade and lower stage BC [84,90]. Other studies pointed out that both telomerase activity [70] and telomerase expression [126] are associated with higher stage and higher grade [70,90]. Preliminary evidence obtained in cell lines suggest that BC might have TERT promoter mutations [53].…”
Section: Telomerase Promoter Mutations In Bladder Carcinomasmentioning
confidence: 99%
“…The in vitro biological assessment of the functional consequence of these mutations, studied by promoter luciferase assay, revealed that their presence results in a two to fourfold increase in telomerase expression [50,53]. Since previously published studies reported high levels of TERT expression in the set of tumours with TERT promoter mutations [70,78,111], it is likely that such alterations may represent one of the missing links between telomerase gene regulation/ reactivation.…”
Section: Telomerase Promoter Mutations and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous in vitro studies have already identified telomerase as a potent tumour-specific promoter, 11,12,30 and 80-90% of adenocarcinoma prostate cells, regardless of stage, are telomerase-positive. [13][14][15][16][17][18] Both the human telomerase RNA (hTR) and the human telomerase reverse transcriptase (hTERT) promoters compared favourably with the strong ubiquitous CMV promoter with respect to their ability to drive the expression of the NAT transgene. In transfected LNCaP cells, the uptake achieved by NAT under the control of the telomerase promoters was similar to that achieved by the neuroblastoma cell line SK-N-BE(2c) which endogenously expresses NAT.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 This is an especially attractive component of gene therapy of prostate cancer since there is increased expression of both the RNA component, human telomerase RNA (hTR), and the protein component, human telomerase reverse transcriptase (hTERT) in cancer cells, including prostate cancer, with little expression in normal cells. [13][14][15][16][17][18] We demonstrate that a targeted tumour-specific radiotherapy/gene therapy strategy with [ 131 I]MIBG for prostate cancer is feasible and could be a promising option for future treatment of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%